(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The purpose of this article is to analyze innovative ideas in the direction of literary studies and translation activities, to determine the place of translation within the framework of a professionally carried out translation technological process.